Employment and education policy for young people in the EU: what can new member states learn from old member states? - Francesco Pastore (Institute for the Study of Labor (IZA), 2007)
The EU experience with youth unemployment has changed over recent years with the launch and re-launch of the Lisbon Strategy and the Bologna process. A dramatic shift has taken place from the 1990s emphasis on labour market flexibility as a tool to abate youth long term unemployment to the more recent stress on the importance of increasing the human capital endowment via a deep reform of education and training systems. This shift is also taking place worldwide, since, as recent studies show, labour market flexibility can increase employability when the human capital level of young people is sufficiently high. To reduce the experience gap between young and adult people, the education systems should become of a higher quality, more inclusive to reduce the dropout rate, homogeneous to other EU countries to favour labour mobility, flexible to allow young people to better find the best match, and contemplate the duality principle, by providing training together with education, to favour smoother school-to-work transitions. Apprenticeships schemes, fiscal incentives to hire the youth unemployed as well as on-the-job training schemes should help reach objectives that cannot be guaranteed simply via an increase in labour market flexibility.
Keywords: I2; 330; Lisbon strategy; employment policy; young people; economic transition; Jugendarbeitslosigkeit; Arbeitsmarktpolitik; Berufsbildungspolitik; Berufseinstieg; Arbeitsmarktflexibilisierung; Lissabon Strategie; EU-Staaten